READING SIMULATION IN YANN MARTEL’S LIFE OF PI - Sri Nurhidayah (POETIKA, 2016)
Yann Martel’s Life of Pi tells a story of a survivor boy floating on a lifeboat with a Bengal tiger passing Pacific Ocean with the brutal show between animals. He is insisted to tell about more realistic story, thus he tells it contains of similar conflicts with different characters; the animals are changed into humans. Here, it shows two stories in one story which blurs the true story behind it. This is what Baudrillard the process of simulation over simulacra; the reproduced false representation of the true reality. The two stories can be both true and thus, the questions can be problematized are; (1) How is simulation understood in Yann Martel’s Life of Pi? (2) What is the hyper-reality resulted as the impact of simulation represented in Yann Martel’s Life of Pi? The used method is objective approach (textually) and based on the analysis, the two stories are connected to each other, animal story represents human story while human story represents the animal story. The animal story can be seen as the false copy of the true story because it copies the human story, so can human story. This is simulation and this simulation results on the two true stories which are hyper-reality.